New workflow and motion analysis for gastric mucosa-associated lymphoid tissue lymphoma on a 1.5-T MR-Linac - Masato Tsuneda; Kota Abe; Yukinao Abe; Yohei Ikeda; Asuka Kodate; Aki Kanazawa; Makoto Saito; Rintaro Harada; Miho Watanabe; Takashi Uno (Technical Innovations & Patient Support in Radiation Oncology, 2025)
We developed and evaluated a multiplane cine magnetic resonance imaging (MRI) workflow for magnetic resonance (MR)-guided online adaptive radiation therapy (MRgOART) for gastric mucosa-associated lymphoid tissue (MALT) lymphoma. Two patients underwent MRgOART using this workflow, which enabled real-time assessments of stomach motion and ensured accurate target coverage within a planning target volume. Our workflow allowed visualization of the stomach with complex intrafractional motion caused by respiration and peristalsis. The total treatment time was clinically acceptable. All fractions satisfied our dose constraints. Our workflow supports precise MRgOART delivery for targets with variable shapes and motion, such as gastric MALT lymphoma.